Truth and consequences - Young, Miriam, 1913-; De Groat, Diane (New York, Four Winds Press, 1975)
A sixth grade girl almost ruins her relationship with her best friend until she learns to temper her honesty with a little tact.
Booklist
Keywords: Honesty -- Fiction; Christmas -- Fiction; Friendship -- Fiction